Physicochemical and sensory analysis of Coalho Cheese supplemented with different concentrations of essential oil of oregano (Origanum vulgare) - BEZERRA, Layla Rodrigues; SARAIVA, Carla Aparecida Soares; DUARTE, Dyalla Correia; SANTOS, Mayle Silva; OLIVEIRA, Juliana Silva de; NETO, Severino Gonzaga; NASCIMENTO, Cleice Kelly dos Santos; BORGES, José Lucas Coutinho; MEDEIROS, Ana Beatriz Azevedo de; RIBEIRO, Neila Lidiany (Food Science and Technology, 2023)
The objective of this study was to analyze the physicochemical, microbiological, and sensory characteristics of coalho cheese supplemented with different concentrations of oregano oil. This study used a completely randomized experimental design with four levels of oregano oil and five storage days. However, fat content and fat in dry matter presented a significant difference (p<0.0001) with the inclusion of oregano oil. The sensory attributes had no significant difference. Regarding sensory analysis and purchase intention, all cheeses were well accepted by most consumers, indicating that they can be used as natural additives in coalho cheese.